2021
DOI: 10.2337/db20-0907
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore 16S Amplicon Sequencing Enhances the Understanding of Pathogens in Medically Intractable Diabetic Foot Infections

Abstract: Diabetic foot infections (DFIs) cause substantial morbidity and mortality. The mainstay of the treatment is empiric antibiotics and surgical debridement in severe cases. In this study, we performed nanopore 16S rDNA sequencing from the debridement specimens of DFIs. Fifty-four surgical debridement specimens obtained from 45 patients with medically intractable DFI were included. The 16S rDNA PCR was performed on each specimen, and Nanopore sequencing was performed for up to 3 h. The reads were aligned to the BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…Nanopore 16S amplicon sequencing is characterized by high sensitivity and specificity and an effective method to detect a pathogen in metagenomics research. [10][11][12] In fact, 16S amplicon sequencing has demonstrated its capability in various clinical cases, [13][14][15][16][17] and we also demonstrated its usefulness for bacterial meningitis in cerebrospinal fluid (CSF) by showing that 16S amplicon sequencing has advantages in the rapid detection of pathogens and the sensitivity after the prior use of antibiotics. 18,19 Thus, nanopore 16S amplicon sequencing has the potential to be practical in cases of suspected infection after neurosurgery as the hastening and sensitive detection of pathogens in central nervous system (CNS) would be helpful in the decision of antibiotics maintenance and stewardship.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Nanopore 16S amplicon sequencing is characterized by high sensitivity and specificity and an effective method to detect a pathogen in metagenomics research. [10][11][12] In fact, 16S amplicon sequencing has demonstrated its capability in various clinical cases, [13][14][15][16][17] and we also demonstrated its usefulness for bacterial meningitis in cerebrospinal fluid (CSF) by showing that 16S amplicon sequencing has advantages in the rapid detection of pathogens and the sensitivity after the prior use of antibiotics. 18,19 Thus, nanopore 16S amplicon sequencing has the potential to be practical in cases of suspected infection after neurosurgery as the hastening and sensitive detection of pathogens in central nervous system (CNS) would be helpful in the decision of antibiotics maintenance and stewardship.…”
Section: Introductionmentioning
confidence: 83%
“…29,32 We expect the result to more accurately reflect the actual clinical situation because the detection of pathogens by 16S amplicon sequencing is less affected by the use of prophylactic antibiotics. 13,16,17,19 Due to its high sensitivity, nanopore 16S amplicon sequencing could help clinicians in ambiguous cases where the bacterial load is lowered. Prophylactic antibiotics are generally administered to patients before and during neurosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevalence of anaerobes may 4) Theoretically, 16S rRNA sequencing may better reflect the true bacterial community of the samples in vivo than traditional culture. Some bacteria grow more rapidly than others during the culture procedure and may come to dominate the composition of the culture; thus, the results of culture may not reflect the true bacterial composition within the sample (Moon et al, 2021). In contrast, 16S rRNA sequencing identifies the pathogenic bacteria of DFIs by processing and analyzing the genomic DNA of samples directly.…”
Section: Discussionmentioning
confidence: 99%
“…[123,124] In recent years, several studies have demonstrated that 16S rRNA gene sequencing using nanopore sequencing technology was feasible and reliable for endometrial microbiome analysis and could supply accurate bacterial taxa assignment. [123,125,126] Hitherto, some strategies based on amplification of 16S rRNA gene and MinION sequencing have successfully utilized to etiologic diagnosis of diseases like empyema, [127] Campylobacter fetus meningitis, [128] bacterial meningitis, [125,129] lower respiratory tract infections, [130] diabetic foot infections, [131] meningitis patients, [127] endophthalmitis [132] and microbial keratitis. [126] Shotgun metagenomic sequencing is an untargeted method that enables to comprehensively sample all genes in all microbes.…”
Section: Diagnostics Of Disease-related Microbiomementioning
confidence: 99%